Impact of board gender composition on corporate debt maturity structures. (4th March 2019) - Li, Yiwei; Zhang, Xiu‐Ye
Abstract: This paper examines the effect of female directors on corporate debt maturity structures. We find that firms with a higher ratio of female directors tend to have a larger proportion of short‐maturity debt. This effect is more pronounced with female independent directors and is insignificant with female inside directors. These findings remain robust under propensity score matching and instrumental variable approaches to address potential endogeneity concerns. Furthermore, we find that our results are driven primarily by firms with weak governance quality and low financial constraints. We also find that the effect does not differ between high‐ and low‐leveraged firms, and there is a negative relation between female directors and likelihood of overinvestment. This evidence suggests that female directors view short‐term debt as a monitoring device.